Life-threatening sustained hypocalcemia following Denosumab use in metastatic prostate cancer. (April 2022) - Patell, Kanchi; Ajay, Kumar; Al Armashi, Abdul Rahman; Bawwab, Ameed; Ravakhah, Keyvan
Introduction: Prostate cancer is the second most frequently diagnosed cancer among men worldwide in 2020. Skeletal-related events (SRE) like pathologic fracture or spinal cord compression are commonly seen in metastatic prostate cancer. Denosumab, a monoclonal antibody, acts by inhibiting osteoclast-mediated bone resorption in bone metastasis from solid tumors and reduces bone turnover and destruction. However, there is an increased risk of life-threatening denosumab-induced hypocalcemia with an incidence of 0.1 to 12.8%. Case report: Our patient is a 69-year-old man with widespread skeletal metastatic disease from primary prostate cancer who presented to the hospital complaining of generalized fatigue and joint pain. Due to severe debilitating low back pain secondary to osteochondral lesions, the patient was started on Denosumab 120 mg. On presentation, serum calcium was found to be severely low at 5.9 mg/dl (serum calcium level prior to Denosumab was 9.1 mg/dl). Management and outcome: Denosumab was discontinued immediately, and the patient was started on IV calcium gluconate. Repeat serum calcium level continued to be low at 6.7 likely due to the long elimination half-life of Denosumab (25–30 days). He was transferred to a long-term acute care facility for long-term IV calcium replacement, where he succumbed to illness six weeks later. Discussion: Denosumab, an anti-resorptive treatment for skeletal metastasis from solid tumors, is shown to cause severe life-threatening hypocalcemia. The maximum serum drug level of Denosumab reaches 7–21 days after administration. Sustained hypocalcemia is rare and life-threatening. Clinicians should use this medication with caution due to its unpredictable side effect profile.